Analysis of Waste Retribution Management in Palupi Village-Palu City, Indonesia - Sagitha, Tiara; Darman, D.; Munawarah, M.; Farid, Erwan Sastrawan (Manunggal Halim Jaya, 2025)
Waste retribution management is important in maintaining environmental cleanliness and ensuring the sustainability of waste management systems in urban areas. Using a descriptive qualitative approach, this study explores the waste retribution management system in Palupi Village, Palu City. The results show that despite the availability of digital payment options, most people still prefer cash payment methods. Low public awareness and lack of transparency in managing retribution funds are the main challenges in optimizing this system. To overcome these obstacles, innovation in payment methods, increased socialization, and the implementation of incentives for the community are needed. By improving the effectiveness of the retribution system, it is expected that waste management in Palupi Village can be optimized, the environment will be kept clean, and community participation in retribution payments will increase.